Influence of carbon nanotubes on photocatalytic activities of titanium dioxide nanocomposite powders - Phuangphaga Daram (2018)
© (2015). This research aims to produce TiO 2 -based composite powder by growing of carbon nanotubes (CNTs) on the surface of micron-sized TiO 2 particles using a chemical vapor deposition (CVD) technique. This nanocomposite powder will be further used as feedstock powder to build up as a coating using a thermal spray technique. This coating is expected to have better photocatalytic efficiency over that of pure TiO 2 coating. For composite powder preparation, rutile-phase of TiO2 powder with particle size in a range of 25-45 μm was used as a starting powder. The powder was placed in a CVD apparatus under ethanol atmosphere as a carbon source. The best CNTs growing condition was found to be 650°C for 60 min. The starting powder and as-synthesized composite powders were characterized by scanning electron microscopy, energy dispersive spectrum, Raman spectroscopy and UV-vis spectroscopy. The results showed that CNTs were successfully grown insitu on the surface of TiO 2 particles. The photocatalytic activities under visible-light were examined based on a degradation of methylene blue. The degradation efficiency of the TiO 2 /CNTs composite powder was found to be higher than that of pure TiO 2 . It is expected that the TiO 2 /CNTs nanocomposite powder could be further used to fabricate various of nanocomposite products.